Community outreach, fundraising, and social transformation: the functions of social media platforms to prevent dating abuse in domestic violence and sexual assault organizations. Issue 3 (3rd July 2021) - Storer, Heather L.; Nyerges, Eva X.; Rodriguez, Maria
ABSTRACT: Social media platforms are essential tools for contributing to feminist social movement building. There has been limited research theorizing how domestic and sexual violence (DV/SA) organizations use social media in their work with youth. Using thematic content analysis, this study interviews DV/SA (n = 35) staff to explore the role of social media in organizational settings. Results indicate that social media is used to advance organizational functionality including publicizing services, fundraising, and youth engagement. There is limited use of movement-oriented hashtags and numerous barriers to social media optimization. This work addresses strategies for expanding social media usage in DV/SA organizations.